2018
DOI: 10.1007/s10753-018-0818-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Taraxasterol on LPS-Stimulated Human Umbilical Vein Endothelial Cells

Abstract: In the present study, we used the human umbilical vein endothelial cells (HUVECs) to investigate the anti-inflammatory effects and mechanism of taraxasterol on vascular inflammation. HUVECs were pre-treated with taraxasterol 1 h before lipopolysaccharide (LPS) treatment. The concentrations of TNF-α, IL-8, PGE2, and NO were measured. The expression of VCAM-1, ICAM-1, iNOS, COX-2, NF-κB, and LXRα was detected by western blot analysis. The results showed that taraxasterol not only reduced the production of TNF-α,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…These results suggested that taraxasterol may exert anti-inflammatory effects via activation of LXRα in the central nervous system. Similarly, another study on LPS-stimulated human umbilical vein endothelial cells also showed that taraxasterol (5–15 μg/ml) exerted anti-inflammatory effects by activating LXRα ( Zheng et al, 2018 ).…”
Section: Pharmacological Profiles Of Taraxasterolmentioning
confidence: 89%
“…These results suggested that taraxasterol may exert anti-inflammatory effects via activation of LXRα in the central nervous system. Similarly, another study on LPS-stimulated human umbilical vein endothelial cells also showed that taraxasterol (5–15 μg/ml) exerted anti-inflammatory effects by activating LXRα ( Zheng et al, 2018 ).…”
Section: Pharmacological Profiles Of Taraxasterolmentioning
confidence: 89%
“…DON has been proven capable of inducing oxidative stress, the inflammatory response, and apoptosis in bovine mammary epithelial cells [ 21 ]. Additionally, the multiple protective effects of taraxasterol, a traditional Chinese herbal medicine, have been explored [ 11 , 19 , 22 , 23 ]. The goal of this research was to explore the underlying mechanisms of the protective effects of taraxasterol.…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxic reactions such as damage lead to cell and tissue damage [28]. Anti-inflammatory treatment could reduced the expression of iNOS in human umbilical vein endothelial cells [29], and endothelial dysfunction get ameliorated via inhibiting iNOS expression [30].…”
Section: Discussionmentioning
confidence: 99%